Importance of Corporate Governance Quality and Voluntary Disclosures of Corporate Governance Information in Listed Malaysian Family Controlled Businesses - Lokman, Norziana; Mula, Joseph M; Cotter, Julie (International Journal of Sustainable Development & World Policy, 2014)
This paper investigates the impact of family control on the association between corporate governance quality and voluntary disclosures of corporate governance information of publicly listed Malaysian family controlled businesses. In addition, the impact of incentive factors are also examined for both family and non-family controlled businesses in relation to voluntary disclosures. The findings suggest that the positive association between corporate governance quality and voluntary disclosures is weaker in family controlled businesses. Stock-based compensation significantly impacts the association.